Cross-Linguistic Transfer and Language Proficiency in the Multilingual Education System of Burundi: What has the Existing Literature so far Discovered? - Dominique Savio Nsengiyumva; Celestino Oriikiriza; Sarah kalyango (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This paper discussed Cross-Linguistic Transfer (CLT) and Language Proficiency in multilingual education in general and highlighted samples of CLT in Burundi as the existing literature reveals. As there exist CLT on all linguistic levels, this discussion has provided examples of phonological (including phonetics), lexical and semantic, and syntactic transfer. It has been realized that there exist a limited number of publications related to CLT among languages studied in the multilingual education system of Burundi. Yet analyses of CLT would supply interesting samples of linguistic features that are likely to be transferred. This would be useful for both language curriculum designers and language policymakers in deciding which language features to supply in language curriculum materials. Furthermore, teachers would find ways of helping learners to improve their language proficiency based on samples of CLT analysis.